Not Lost in Translation: Neural Responses Shared Across Languages - Honey, Christopher J. (Society for Neuroscience, 2012)
How similar are the brains of listeners who hear the same content expressed in different languages? We directly compared the fMRI response time courses of English speakers and Russian speakers who listened to a real-life Russian narrative and its English translation. In the translation, we tried to preserve the content of the narrative while reducing the structural similarities across languages. The story evoked similar brain responses, invariant to the structural changes across languages, beginning just outside early auditory areas and extending through temporal, parietal, and frontal cerebral cortices. The similarity of responses across languages was nearly equal to the similarity of responses within each language group. The present results demonstrate that the human brain processes real-life information in a manner that is largely insensitive to the language in which that information is conveyed. The methods introduced here can potentially be used to quantify the transmission of meaning across cultural and linguistic boundaries.